(untitled) (Journal of Surgical Sciences, 2019)
Background: Bronchodilator P2selective adrenergic drug-salbutamol) causes bronchodilation and increases the vital capacity, tidal volume and total lung capacity and reduces gas trapping. Use of bronchodilator in patients undergoing Off-pump coronary artery bypass graft (OPCABG) may lead to better preservation of pulmonary function. Objective: To evaluate the role of bronchodilator on preservation of post-operative pulmonary function in patients who underwent OPCABG. Methods: This study was conducted on 50 patients randomized into two groups to assess the pulmonary function after off-pump CABG. Among them, 25 patients (group-I) were treated by preoperatively bronchodilator and compared them with other 25 patients (group-II) who were not treated by preoperative bronchodilator. We compared arterial blood gas analysis, duration of total mechanical ventilation, days spent in the surgical ICU and spirometric indices. Results: Mean±SE value of mechanical ventilation time after operation in group-I was 14.25±0.85 hours and in group-II was 16.88±0.85 hours. Mean±SE value of ICU stay after surgery was 98.64±2.07 hours in group I and 110.56±2.36 hours in group-II. Both results were statistically significant (P=0.042 and P=0.001 respectively). The FVC and FEV1 after admission were not statistically significant (P>0.05). On the day before surgery the values of FVC and FEV1 were increased (more in group-1 who were treated with bronchodilator) and 7th postoperative day the value were decreased (more in group -11 who were not treated with bronchodilator). The results were found statistically significant in between two groups (P<0.05). Significant difference were found in PaO2 and PaCO2 on arterial blood gas analysis at half an hour after extubation and on 1st POD (P<0.05). Mean±SE value of postoperative hospital day in group-1 was 8.88±0.24 days and in group II was 10.14±0.43 days which was found statistically significant (p=0.014). Among post-operative pulmonary complications, in group 1, one (4%) patient was found with pleural effusion and one (4%) patient with atelectasis. but in group-II, one (4%) patient was found with pleural effusion and five (20%) patients were found with atelectasis. Conclusion: Use of bronchodilator preoperatively in patients who underwent OPCABG with impaired pulmonary function leads to reduced mechanical ventilation time, less ICU stay after surgery, better preservation of pulmonary function, reduced post-operative pulmonary complications and reduced hospital stay. Journal of Surgical Sciences (2014) Vol. 18 (2) : 51-56